Genetic risk factor APOEε4 associates with plasma amyloid beta in amnestic mild cognitive impairment and alzheimer’s disease (Faculty of Medicine Universitas Indonesia, 2016)
Background: APOEε4 is a strong genetic risk factor for Alzheimer’s disease (AD). AD itself has been associated with reduced Aβ clearance from the brain and plasma. Understanding the potential pathogenic link between APOEε4 and plasma Aβ might allow for earlier identification of people at risk of developing AD. The aim of this study is to find out the correlation between APOEε4 and plasma Aβ in amnestic mild cognitive impairment (aMCI) and AD patients. Methods: This is a comparative cross-sectional study of patients attending a memory clinic in Siloam Hospital Lippo Karawaci, Tangerang, during the period of 2013-2014. Subjects were categorized into three categories: normal aging, aMCI, and AD. We performed blood test to examine APOEε4, plasma Aβ4o level, and plasma Aβ42 level. All data analyses were performed using correlation test and logistic regression. Results: Sixty subjects (normal aging = 23, aMCI = 17, AD = 20) were included. There were 19 (31.7%) subjects with APOEε4 positive. Subjects carrying ε4 allele were more likely to have AD by 3.9-fold than subjects with APOE ε4 allele negative. There is a significant difference between the mean of plasma Aβ40 in aMCI group and AD group. We also found correlation between APOEε4 (+) and higher plasma Aβ42 (p<0.05). Conclusion: There is a correlation between APOEε4 and plasma Aβ42 level, which supports the hypothesis that this genetic isoform accelerates the rate and progression of AD through Aβ-dependent pathways.